Sharing Knowledge Dan Studi Tiru Budi Daya Jamur Untuk Peningkatan Pendapatan - Arifin, Zainul; Bunyamin, Bunyamin; Munfaqiroh, Siti; Sa’adah, Lailatus; Erawati, Sherly Hesti; Sugiono, Djoko (Jurnal ABM Mengabdi, 2023)
The service activities at "Omah Jamur Ayu" are a continuation of the business school activities held by "Lazis Sabilillah" and in collaboration with "STIE Malangkucecwara Malang" and other partners. The aim of this service activity is to carry out a study to imitate the experience and success of the achievements made by Omah Jamur Ayu. This mock study was carried out with the aim of bringing benefits, increasing synergy and building cooperation with MSMEs assisted by Sabilillah. The method used was by conducting program outreach, providing materials, training and mentoring. As a result of this activity, MSME participants gained knowledge about developing mushroom seeds, caring for the mushroom growth process, harvesting mushrooms and managing mushrooms into processed dishes that are ready to be served in restaurants. The training material includes making crispy mushrooms with various flavors, namely BBQ, blackpaper and teriyaki; various soups (Ayu mushroom tomyum, Ayu mushroom capjay, Ayu mushroom asparagus) and various snacks (mushroom brontak, mushroom samosa and mushroom lumpiah) trained by experienced trainers